Analisis Penulisan al-Kâmil fî al-Târîkh Karya Ibn al-Atsir - Shidqy Munjin; Satria Setiawan (Rihlah : Jurnal Sejarah dan Kebudayaan, 2018)
Al-Kâmil fî al-Târīkh is the most important work of Ibn al-Athir. Ibn al-Athir wrote this work by collecting data from his predecessors and adding to the events that occurred during his time. Ibn al-Athir wrote down all the events witnessed by his own eyes, especially those relating to the saliibn war. This paper attempts to analyze and compare the work of Ibn al-Athir in terms of historical aspects that developed in the Islamic world during his time, especially with Târikh al-Rusul wa al-Muluk by Ibn Jarir al-Tabari. The research method used in this study was library research, where the study was explained descriptively and critically analyzed. Then the type of data used is literature literary data, both primary and secondary. The results of this study indicate that Ibn al-Athir with his work al-Kâmil fî al-Tîrīkh was a initiator of a new historical study in the Islamic world. Al-Kâmil fî al-Târîkh merupakan karya terpenting dari Ibn al-Atsir. Ibn al-Atsir menulis karyanya ini dengan mengumpulkan data-data dari para pendahulunya dan ditambahkan dengan kejadian yang terjadi pada masanya. Ibn al-Atsir menuliskan semua kejadian yang disaksikan oleh matanya sendiri, terutama yang berkaitan dengan perang saliibn Tulisan ini mencoba menganalisis dan membandingkan karya Ibn al-Atsir tersebut ditinjau dari aspek ilmu kesejarahan yang berkembang  di dunia Islam pada masanya, terutama dengan Târikh al-Rusul wa al-Muluk karya Ibn Jarir al-Thabari. Metode penelitian yang digunakan dalam kajian ini adalah riset kepustakaan, dimana kajiannya dijelaskan secara deskriptif dan analisis kritis. Kemudian jenis data yang digunakan adalah data literer kepustakaan, baik primer maupun sekunder. Hasil penelitian ini menunjukkan bahwa Ibn al-Atsir dengan karyanya al-Kâmil fî al-Târîkh merupakan seorang penggagas kajian kesejarahan yang baru dalam dunia Islam.